2008
DOI: 10.1088/0960-1317/18/2/025021
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication, characterization and testing of a MEMS circular diaphragm mass sensor

Abstract: This paper presents a discussion on the fabrication, characterization and testing of a degenerate mode resonant mass sensor which takes the form of a crystalline silicon MEMS circular diaphragm. The device is fabricated from the device layer of a SOI wafer which is bonded anodically to a Pyrex substrate. The efficacy of the fabrication process is assessed. Characterization of the diaphragm is performed by actuating the diaphragm electrostatically and measuring its response using optical surface profilometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…10. This was in accordance with what was previously observed during characterization of large die devices, in which severe vibrational damping was present in devices tested at atmospheric pressure [6]. Moreover, a similar damping effect has been reported by Pandey et al [10].…”
Section: Packaging and Integration Of The Device Into A Microfluidsupporting
confidence: 92%
See 3 more Smart Citations
“…10. This was in accordance with what was previously observed during characterization of large die devices, in which severe vibrational damping was present in devices tested at atmospheric pressure [6]. Moreover, a similar damping effect has been reported by Pandey et al [10].…”
Section: Packaging and Integration Of The Device Into A Microfluidsupporting
confidence: 92%
“…The current die layout of 2mm x 2mm is better suited to PCB packaging than the 15mm x 5mm die previously presented and designed for dual in-line packaging [6]. The CDR device layout and diaphragm details are shown in Fig.…”
Section: A Mems Device Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…To first order it can be shown that structures with cyclic symmetries of order p, which break this degeneracy are determined by the condition 2n=p ¼ 1; 2; 3; :::. 6 When mass or stiffness is added to p identical sectors of the resonator, then the degeneracy is broken and the single resonant frequency "splits" to yield two, close, resonant frequencies. This frequency split is used to record the added mass.…”
Section: A Modal Degeneracymentioning
confidence: 99%